Redefining and Improving Patient Safety - Ball, M. J.; Douglas, J. V. (Methods of Information in Medicine, 2002)
Objectives: The Institute of Medicine (IOM) has focused attention on patient safety in the united States. Other countries share these concerns.Methods: Governmental agencies and professional organizations are redefining approaches to safety, calling upon the use of information and communication technology as an enabler and expanding the range of evidence admissible in documenting success.Results: Efforts to understand medical errors have used retrospective chart review, incident reporting, and computerized surveillance; the result is an evolving picture of the number, nature, and cause of errors. Approaches used to prevent errors include computerized physician order entry, decision support tools, computerized monitoring, and evidence-based practice; varying levels of evidence document their success.Conclusions: Technology offers challenging capabilities, not simple solutions. New evidence and new tools demand new approaches and attention to human factors.
Keywords: Patient safety; medical errors; decision support; qualitycare; medical informatics